Comparative Study of Maintenance and Recovery Characteristics of Sevoflurane and Isoflurane in Neurosurgery - Fatema Vali, Lulu; M. Khobragade, Sonali (Academia Anesthesiologica International, 2019)
Background: Rapid recovery is very important in neurosurgical patients for early neurological assessment. The purpose of this study was to compare the maintenance and recovery characteristics of two most commonly used volatile anaesthetic agents, Isoflurane and Sevoflurane in neurosurgery patients. Subjects and Methods: A hospital based, prospective, randomized, comparative study was undertaken in tertiary care centre for a period of two years after institutional ethical committee approval. The study included 60 patients undergoing neurosurgical surgeries in general anaesthesia. After intravenous induction, maintenance was achieved by inhalational anaesthetic agent according to randomly allocated group. Haemodynamic parameters like heart rate, systolic blood pressure, diastolic blood pressure along with recovery time and complications were studied and p<0.05 was considered significant on statistical analysis. Results: The pulse rate was significantly less in sevoflurane group than isoflurane group from 20 min to 120 min (p<0.05). The mean systolic and diastolic blood pressure were comparable in both the groups except the systolic and diastolic blood pressure were lower in Sevoflurane group than Isoflurane group at 5 min(p<0.05). The mean emergence time and extubation time were significantly shorter in Sevoflurane group than Isoflurane group(p<0.001).Conclusion: Sevoflurane provides stable haemodynamics during maintenance of anaesthesia and allows rapid recovery for faster postoperative basic neurological assessment.